PENGARUH KETERLIBATAN PEMANGKU KEPENTINGAN TERHADAP PENGUNGKAPAN LAPORAN KEBERLANJUTAN BERDASARKAN GLOBAL REPORTING INITIATIVE (GRI) G4 - Qisthi, Fadhliatul; Fitri, Meutia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The purpose of this study is to determine whether there is any influence from the involvement of shareholders, employees, government, and media on the disclosure of sustainability reports based on GRI-G4. This study uses multiple regression linear methods with a quantitative causality study design supported by secondary data. Sample taken by the method of purposive sampling with the number of 35 companies listed in the Indonesia Stock Exchange in 2016-2019 and discovered140 sustainability report. The data collection technique used in this research is documentation. The results of this study indicate that companies that get shareholder involvement have a positive and significant effect on the disclosure of sustainability reports. It is suggested that shareholders react to the disclosure of sustainability reports which is pushed from the financial market so that the level of shareholder confidence increases by increasing the level of report disclosure. Meanwhile, the involvement of employees, government, and media has no effect on disclosure of sustainability report. This is because employees tend to think that social responsibility can add to the burden companies so that they can reduce their salarie, as well as weaknesses related to the regulations for disclosing sustainability reports and the media are platforms that are misused by people in Indonesia.